Optimal Systolic Blood Pressure Control After Thrombectomy in Acute Ischemic Stroke: A Systematic Review and Meta-analysis - Baikuntha Panigrahi; Rohit Bhatia; Partha Haldar; Risha Sarkar; Imnameren Longkumer (Annals of Indian Academy of Neurology, 2025)
Background and Objectives: The optimal systolic blood pressure (SBP) control after endovascular thrombectomy (EVT) is unclear. This study aimed to determine whether intensive SBP control (<140 mmHg) within 24 h post-EVT, compared to conventional management (<180 mmHg), leads to a better functional outcome, defined as a modified Rankin Scale (mRS) score of 0–2 at 90 days. Methods: Following Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines, we searched databases (PubMed, Scopus, EMBASE, Google Scholar, Web of Science) for English language articles up to March 15, 2024. We included randomized controlled trials (RCTs) and observational studies comparing intensive versus conventional SBP control up to 24 h post-EVT. Studies without separate primary outcome data and case series/reports were excluded. The primary outcome was functional independence (mRS 0–2 at 90 days). Results: Twelve studies (n = 5152 patients; five RCTs and seven observational studies) were included, and a primary analysis of the RCTs, along with a secondary exploratory analysis of the observational studies were conducted. The analysis of RCTs favored conventional control for the primary outcome (risk ratio [RR]- 0.81; 95% confidence interval [CI]- 0.73–0.90; P < 0.0001). Mortality rates (RR- 1.14, 95% CI- 0.89–1.45; P = 0.29) and the risk of symptomatic intracranial hemorrhage (RR- 1.10, 95% CI- 0.77–1.58; P = 0.60) were similar in both groups. The secondary exploratory analysis of observational data favored the intensive arm for the primary outcome (RR- 1.28, 95% CI- 1.17–1.41; P < 0.00001). Conclusions: Our primary analysis of RCTs showed that intensive control was associated with poorer functional outcomes, with no significant impact on mortality rate or the risk of symptomatic intracranial hemorrhage. Although observational studies suggested better outcomes with intensive control, we recommend conventional management based on Level 1 evidence from RCTs. PROSPERO Registration no- CRD42023463173